2017
DOI: 10.7754/clin.lab.2017.170125
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Based Identification of a Carbonized Victim by Kinship Analysis

Abstract: Body fluids (blood, saliva) represent a better source for DNA compared to hard tissue, and its processing times are shorter than those for bone or teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…After the DNA separation, we obtained the electropherograms and the genotypes of the unidentified person and his alleged brothers using the Gene Mapper ID-X software version 1.4 (Applied Biosystems, USA). GenoProof 3 Software-Kinship Examination (Qualitype GmbH, Dresden, Germany) [14] was used for the statistical part. In this case, a full sibling probability of 99.999972% was obtained between the woman and her presumptive brother.…”
Section: Resultsmentioning
confidence: 99%
“…After the DNA separation, we obtained the electropherograms and the genotypes of the unidentified person and his alleged brothers using the Gene Mapper ID-X software version 1.4 (Applied Biosystems, USA). GenoProof 3 Software-Kinship Examination (Qualitype GmbH, Dresden, Germany) [14] was used for the statistical part. In this case, a full sibling probability of 99.999972% was obtained between the woman and her presumptive brother.…”
Section: Resultsmentioning
confidence: 99%
“…An important aspect to look out for while performing genetic identification of skeletonized remains relates to the relationship between the types of bones and the DNA concentration obtained during the analysis. Many studies have demonstrated that compact bones yield a greater amount of DNA when compared to spongy bones [11][12][13]. In Tables 4-6, the genetic profiles obtained from bones remains are presented together with the genetic profiles of the first degree relatives, thus being demonstrated the kinship relationship between them.…”
Section: Discussionmentioning
confidence: 99%